Development of tools for managing professional risk at enterprises and reducing the possibility of threats to employees’ health - Sevastyanov, Boris; Shadrin, Robert; Dolinina, Irina (Nexo Revista Científica, 2022)
When checking organizations by executive authorities, special attention is paid to the availability of documents related to the assessment of professional risks. One such document is the register of identified hazards for each profession. The work considers the development of a standard register using the example of a milk pasteurization and cooling apparatus operator. The choice of a profession is based on an assessment of accidents that have occurred at the enterprise - most of it relates to this profession, and a varied list of hazards arising in the course of the technological process and the performance of work duties. The developed register contains identified hazards, grouped into categories according to the primary source of hazard: mechanical, thermal, electrical, associated with microclimate, chemical and biological nature, associated with aerosols of fibrogenic action, noise, vibration, lighting of the working area, the severity and intensity of labor, process, transport, fire and explosion. The model register is part of the regulation on the OSH management system at the enterprise. It can be used in the same way as the standard OSH instructions. The list of identified hazards applies to most of the occupations in the workshop. Typical registries will reduce the time spent on their development in the organization.